Geophysical Imaging of Lithology of a Coastal South Indian Block for Aquifer Conservation and Management - et. al., A.Amuthini Sambhavi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Manifold inflation in the usage of groundwater has fostered us to meet out this study to throw light on the aquifer zones of Thirukkazhukundram Block, Tamil Nadu, India to validate the subsurface lithological layers interms of resistivity and thickness. Hence, a geophysical resistivity survey aligned to Schlumberger array was conducted in 30 grided villages of the study domain. IPI2Win and ArcGIS softwares supported the study. The first to fifth layer iso resistivity and first to fourth layer thickness maps reveal the water storage zones to aid in water resource management. Researchers, policy makers, and government obviously profit from this study to sustain and conserve water by recharging